Strategies to Increase Parents' Awareness of Stunting Prevention: Community Service Initiatives in Riau Province in Supporting the Sustainable Development Goals (SDGs) - Yusnarida Eka Nizmi; Yessi Olivia; Rahmi Yulia; Tuah Kalti Takwa (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The community service activity aims to enhance the understanding of parents and young couples regarding stunting and the importance of ensuring that children are free from this issue to achieve the Sustainable Development Goals (SDGs) in Riau Province. The primary challenge faced is the low level of knowledge about stunting and its impacts, which can lead to nutritional deficiencies that potentially affect children's health and intellectual development. The method employed in this initiative is an interactive workshop involving 50 participants, including parents, prospective parents, and healthcare professionals. This activity is conducted in collaboration with the local Health Department, which serves as a partner to provide materials and facilitators. Evaluation is carried out through pre-tests and post-tests to assess participants' knowledge improvement, as well as surveys regarding changes in attitudes and behaviors related to child nutrition. Data collection methods include questionnaires and interviews as primary data, along with literature reviews as secondary data. The results achieved from this activity indicate an 80% improvement in participants' understanding of stunting prevention, as well as positive changes in parenting practices and children's nutritional intake. Through this initiative, it is hoped that the community will become more cognizant of the importance of nutrition during the first 1,000 days of life, which can lead to a healthier and more qualified generation.Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman orang tua dan pasangan muda mengenai stunting serta pentingnya memastikan anak-anak bebas dari masalah ini guna mencapai Tujuan Pembangunan Berkelanjutan (Sustainable Development Goals/SDGs) di Provinsi Riau. Masalah yang dihadapi adalah rendahnya pengetahuan tentang stunting dan dampaknya, yang dapat mengakibatkan anak-anak mengalami defisiensi gizi yang berpotensi mempengaruhi kesehatan dan perkembangan intelektual mereka. Metode yang digunakan dalam pengabdian ini adalah workshop interaktif dengan melibatkan 50 peserta, termasuk orang tua, calon orang tua, dan tenaga kesehatan. Kegiatan ini bekerja sama dengan Dinas Kesehatan setempat sebagai mitra untuk memberikan materi dan fasilitator. Evaluasi dilakukan melalui pre-test dan post-test untuk mengukur peningkatan pengetahuan peserta, serta survei mengenai perubahan sikap dan perilaku terkait gizi anak. Metode pengumpulan data dilakukan dengan mengisi angket dan wawancara sebagai data primer, serta studi pustaka sebagai data sekunder. Hasil yang telah dicapai dari kegiatan ini menunjukkan peningkatan pemahaman peserta tentang pencegahan stunting sebesar 80%, serta perubahan positif dalam pola asuh dan asupan gizi anak. Melalui kegiatan ini, diharapkan masyarakat lebih sadar akan pentingnya gizi dalam 1000 hari pertama kehidupan, yang dapat berdampak pada generasi yang lebih sehat dan berkualitas.